A Computational Mechanistic Investigation into Reduction of Gold(III) Complexes by Amino Acid Glycine: A New Variant for Amine Oxidation. Issue 33 (16th May 2018) - Chipman, Antony; Gouranourimi, Ali; Farshadfar, Kaveh; Olding, Angus; Yates, Brian F.; Ariafard, Alireza
Abstract: Density functional theory (DFT) was utilized to explore the reduction of gold(III) complexes by the amino acid glycine (Gly). Interestingly, when the nitrogen atom of Gly coordinates to the gold(III) center, its C α ‐hydrogen atom becomes so acidic that it can be easily deprotonated by a mild base like water. The deprotonation converts the amino acid into a potent reductant by which gold(III) is reduced to gold(I) with a moderate activation energy. To our knowledge, this is the first contribution suggesting that primary amines are oxidized to imines via direct α‐carbon deprotonation. This finding may provide new insights into the mechanistic interpretation of amine oxidations catalyzed/mediated by a center with high cathodic reduction potential. This work also provides a rationalization behind why gold(III) complexes with amine‐based polydentate ligands are reluctant to undergo a redox process. Gold(III) reduction occurs most efficiently if the C α proton leaves in the plane of the C α, N and Au atoms. Chelation prevents this alignment, resulting in the gold(III) complex being unreactive toward reduction. It has been experimentally found that gold(III) is capable of oxidizing Gly to glyoxylic acid (GA) as the initial product. The latter, in the presence of another gold(III) complex, has been reported to undergo oxidative decarboxylation to afford CO2 and HCOOH. This process is found to be mediated by formation of a geminal diol intermediate produced by reaction of water with the aldehyde functional group of the coordinated GA. Abstract : Amine oxidation : Coordination of an amino acid to gold(III) renders its C α ‐hydrogen so acidic that it can be deprotonated by a mild base such as water, resulting in reduction of gold(III) to gold(I) and formation of a protonated imine.